2010
DOI: 10.1007/s11671-010-9543-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanofabrication with Pulsed Lasers

Abstract: An overview of pulsed laser-assisted methods for nanofabrication, which are currently developed in our Institute (LP3), is presented. The methods compass a variety of possibilities for material nanostructuring offered by laser–matter interactions and imply either the nanostructuring of the laser-illuminated surface itself, as in cases of direct laser ablation or laser plasma-assisted treatment of semiconductors to form light-absorbing and light-emitting nano-architectures, as well as periodic nanoarrays, or la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 71 publications
(93 reference statements)
1
77
0
Order By: Relevance
“…This is in agreement with our observation that MgO could form hollow particles by pulsed laser ablation of Mg in water but Mg(OH) 2 did not [147]. Similar hollow particles have been observed in the products of pulsed laser ( = 800 nm) ablation of Ti target in water [189], and in the products of pulsed laser ( = 1047 nm) ablation of ␣-Al 2 O 3 in water [17]. And very recently, Yang et al reported the fabrication of hollow carbon and carbide particles by pulsed laser ( = 1064 nm) ablation of tungsten or silicon targets in ethanol or toluene [190,191], which were also considered to form on bubbles.…”
Section: Hollow Particlessupporting
confidence: 92%
“…This is in agreement with our observation that MgO could form hollow particles by pulsed laser ablation of Mg in water but Mg(OH) 2 did not [147]. Similar hollow particles have been observed in the products of pulsed laser ( = 800 nm) ablation of Ti target in water [189], and in the products of pulsed laser ( = 1047 nm) ablation of ␣-Al 2 O 3 in water [17]. And very recently, Yang et al reported the fabrication of hollow carbon and carbide particles by pulsed laser ( = 1064 nm) ablation of tungsten or silicon targets in ethanol or toluene [190,191], which were also considered to form on bubbles.…”
Section: Hollow Particlessupporting
confidence: 92%
“…113 It is anticipated that controlled laser irradiation of a sample of Ag colloids, in the presence of appropriate chemical species, could lead to a straightforward method for fabricating Ag nanostructures with well-defined and controllable shapes. 114 …”
Section: Preparation Of Silver Nanostructuresmentioning
confidence: 99%
“…112,114,123126 Recent mechanistic studies suggest that the reaction, in its most basic configuration, requires citrate, oxygen, and light as shown in Figure 5A. The proposed mechanism is as follows: 56,124 First, LSPR excitation induces photo-oxidation in citrate molecules adsorbed on the surface of the nanostructure.…”
Section: Preparation Of Silver Nanostructuresmentioning
confidence: 99%
“…The LB technique provides one of the few methods of preparing organized assemblies of monolayers, which are prerequisite in various applications where high-accuracy spatially resolved methods are needed [33]. Such monolayers made with transparent microspheres find applications in the structuration of bulk substrates, resulting in either nanohole or nanobump arrays [34][35][36][37][38][39], but have also been explored in the literature in the context of electronics, optics, microlithography, chemical sensors, and biosensors [32][33][34][35][36][37][38][39][40][41]. It has been demonstrated that properly coated nanoparticles can be organized at the air-water interface by using the same procedure.…”
Section: Langmuir-blodgett Filmsmentioning
confidence: 99%